BUSINESS PROSPECTS FOR CULTIVATION OF OYSTER (Crassostrea gi-gas) IN OKAYAMA, JAPAN - Fairuz Romdhony Desnefa Anwar; Ine Maulina (Jurusan Perikanan dan Kelautan, 2022)
Japan is known as one of pioneering countries in oyster cultivation. This study aims to reveal the prospects for the cultivation of pacific oysters. The analysis of investment evaluation criteria in this study is based on financial analysis methods which include Benefit-Cost Ratio (BCR), Break Even Point (BEP), Return of Investment ROI, and Payback Period. The process carried out in the oyster cultivation steps starts from spawning and oyster fry, growth control (Yokusei), hanging (Hansuika) and seeding (Tanetsuke), check growth and landing and marketing. Based on the results of data analysis, it is obtained that the values of BCR, BEP, ROI, and Payback Period respectively are 1.88, 1,155.5 kg, 47%/year, 25.6 months. In this analysis, it is obtained that the BCR value is more than 1, so the business prospects for the oyster cultivation are very feasible to do. The benefit of this study is that the description of prospects and the financial analysis presented can be a consideration and reference for people who have an interest in oyster farming, especially for small-scale businesses.